Morphological variability of Carex ×vratislaviensis (Cyperaceae) and its parent species—case from Central Europe - Řepka, Radomír; Řepka, Jan; Šebesta, Jan; Taraška, Vojtěch (Phytotaxa, 2026)
The article analyzes morphological variability and the possibility of distinguishing the hybrid sedge Carex ×vratislaviensis and its wetland parent species C. acuta and C. buekii in Central Europe. A large amount of data was obtained from herbarium material by measuring or evaluating 14 quantitative traits, 2 ratios and 8 qualitative features in 32 populations of the three taxa collected in Central Europe. The data were analysed by Dunn’s test and discriminant function analysis (DFA). Specimens of C. acuta, C. buekii and C. ×vratislaviensis form three clearly separate groups distinguishable by combination of 8 features: utricle length, presence of veins on the utricle surface, length of lowest inflorescence bract, width of female spikes, leaf width, stem length, spikes fertility and presence of the interrupted base of lowest female spike. The analysis also confirms the assumption of extensive variability of hybrid populations observed in the field. Intermediate morphotypes as well as variable plants closer to one or the other parent species are common. The length of the lower inflorescence bract, the length of the peduncle of the lower female spike, the length of the inflorescence and the length of the utricle are the traits that best characterize the studied hybrid.